An ethnobotanical analysis on flora-medicine continuum among the tribal inhabitants of Ratnagiri and Palghar district, Maharashtra, India - Roy, Anirban; Janbandhu, Supriya (Ethnobotany Research and Applications, 2020)
Background: Considering the applicability of wild plants in the pharmaceutical industries, two tribal predominant areas of Maharashtra- Sangameshwar Taluka (Ratnagiri district) and Saphale village (Palghar district) - were chosen to document the local traditional knowledge about medicinal plants. Methods: The ethnomedicinal data were collected through a questionnaire-based survey and extensive personal dialogues adopting the chain sampling referral method with native villagers and Hakims (Traditional healers). The field-based investigations were carried out from September 2017 to April 2018 under the regulatory directives of K.J. Somaiya College of Science and Commerce (Autonomous- affiliated to University of Mumbai). Results: A total of 51 Traditional Medicinal Plants (TMPs) were documented from the responses of 92 inhabitants in the study areas. The investigators taxonomically categorized these plants into their botanical families, yielding the results- 22 dicot families, 7 monocot families, 2 magnoliids, and 1 pteridophytic family- for the present study. Results revealed that leaves were the most frequently used medicinal part of the documented species and decoction was the most commonly prepared medicinal formulation. Conclusion: Of the 51 TMPs, six medicinal plants- Adhatoda vasica, Aloe vera, Ampelocissus latifolia, Glossocardia bosvallia, Ricinus communis, and Woodfordia fruticosa - were found to be common in both the study regions. We believed that social factors tend to influence the traditional medicinal knowledge since the same plants were known by different names for treating two unlike ailments. Highest use reports were observed for Terminalia paniculata in Sangameshwar Taluka (Ratnagiri district) and Ampelocissus latifolia in Saphale village (Palghar district). The study realised the fact that both the areas were rich in floral vegetation with interminable floral diversity but remained botanically virgin and unexplored neither for medicinal nor for scientific endeavors. Keywords: Ethnobotany, Traditional medicinal plants (TMPs), Tribal, Hakims, Maharashtra